Equações balanceadas no dia anterior |
2 KCl = K2 + 2 Cl
H2C6H6O6 + H2O = H3O + HCO =>
H2C6H6O6 + 2 H2O = 2 H3O + 6 HCO
MnO2 + HCl = Mn + Cl + H2O =>
MnO2 + 4 HCl = Mn + 4 Cl + 2 H2O
NaOH + H3Po4 = (Na)3Po4 + H2O =>
3 NaOH + H3Po4 = (Na)3Po4 + 3 H2O
Mg(CH3COO)2 + NaOH = Mg(OH)2 + (CH3COO)Na =>
Mg(CH3COO)2 + 2 NaOH = Mg(OH)2 + 2(CH3COO)Na
Sn + HClO4 = Sn(ClO4)4 + H =>
Sn + 4 HClO4 = Sn(ClO4)4 + 4 H
NaIO4 + MnSO4 + H2O = NaIO3 + MnO2 + H2SO4 =>
NaIO4 + MnSO4 + H2O = NaIO3 + MnO2 + H2SO4
BaSO4 + Al = BaS + Al2O3 =>
3 BaSO4 + 8 Al = 3 BaS + 4 Al2O3
Au(s) + Cl2(g) = AuCl3(s) =>
2 Au(s) + 3 Cl2(g) = 2 AuCl3(s)
Na + Cl1 = Na1Cl1 =>
Na + Cl1 = Na1Cl1
BaCl2 + C14H14N3NaO3S = Ba(N3NaO3S)2 + C14H14Cl =>
BaCl2 + 2 C14H14N3NaO3S = Ba(N3NaO3S)2 + 2 C14H14Cl
Cu(NO3)2(aq) + S(aq) = CuS(s) + NO3(aq) =>
Cu(NO3)2(aq) + S(aq) = CuS(s) + 2 NO3(aq)
Ba + SO4 = Ba4SO4 =>
4 Ba + SO4 = Ba4SO4
AlCl3 + HOH = AlOHCl2 + HCl =>
AlCl3 + HOH = AlOHCl2 + HCl
K2CrO4 + H2SO4 = K2H2 + CrO4(SO4) =>
K2CrO4 + H2SO4 = K2H2 + CrO4(SO4)
CrCl3 + Mn(NO3)2 = MnCl2 + Cr(NO3)3 =>
2 CrCl3 + 3 Mn(NO3)2 = 3 MnCl2 + 2 Cr(NO3)3
Al(ClO2) + Na(AsO4) = Al(AsO4) + Na(ClO2) =>
Al(ClO2) + Na(AsO4) = Al(AsO4) + Na(ClO2)
AlCl3 + HOH = AlOHCl2 + HCl =>
AlCl3 + HOH = AlOHCl2 + HCl
LiCl + Na2 + Co3 = LiCo3 + Na2Cl =>
LiCl + Na2 + Co3 = LiCo3 + Na2Cl
KI3 + Cu = CuI + KI2 =>
KI3 + Cu = CuI + KI2
NH4ClO4 + C12H22O11 = Cl2 + N2 + H2O + CO2 =>
12 NH4ClO4 + C12H22O11 = 6 Cl2 + 6 N2 + 35 H2O + 12 CO2
CH3CH2CH2OH + KMnO4 + H2SO4 = CH3CH2COOH + K2SO4 + MnSO4 + H2O =>
5 CH3CH2CH2OH + 4 KMnO4 + 6 H2SO4 = 5 CH3CH2COOH + 2 K2SO4 + 4 MnSO4 + 11 H2O
Na + H2O = NaHO2 + H2 =>
2 Na + 4 H2O = 2 NaHO2 + 3 H2
CO2 + NaOH = Na2CO3 + H2O =>
CO2 + 2 NaOH = Na2CO3 + H2O
K2Cr2O7 + Cl2 = KCl + CrCl3 + Cl2O7 =>
K2Cr2O7 + 5 Cl2 = 2 KCl + 2 CrCl3 + Cl2O7
Cu(SO3)2 + NaOH = Cu(OH)2 + NaSO3 =>
Cu(SO3)2 + 2 NaOH = Cu(OH)2 + 2 NaSO3
(CuOH)2SO4 = CuOH + SO4 =>
(CuOH)2SO4 = 2 CuOH + SO4
KCrO4 + Cl2 + KOH = KCrO2 + KClO3 + H2O =>
5 KCrO4 + 2 Cl2 + 4 KOH = 5 KCrO2 + 4 KClO3 + 2 H2O
Cu(SO3)2 + NaOH = Cu(OH)2 + NaSO3 =>
Cu(SO3)2 + 2 NaOH = Cu(OH)2 + 2 NaSO3
XI4O4 + H2C2O4 = X2C6O12 + I2 + CO2 + H2O =>
2 XI4O4 + 8 H2C2O4 = X2C6O12 + 4 I2 + 10 CO2 + 8 H2O
Cu(SO3)2 + NaOH = Cu(OH)2 + NaSO3 =>
Cu(SO3)2 + 2 NaOH = Cu(OH)2 + 2 NaSO3
AgNO3(aq) + Ba(OH)2(aq) = Ag2O(aq) + Ba(NO3)2(aq) + H2O(l) =>
2 AgNO3(aq) + Ba(OH)2(aq) = Ag2O(aq) + Ba(NO3)2(aq) + H2O(l)
HF + BaS = BaF2 + H2S =>
2 HF + BaS = BaF2 + H2S
Cu(SO3)2 + NaOH = Cu(OH)2 + NaSO3 =>
Cu(SO3)2 + 2 NaOH = Cu(OH)2 + 2 NaSO3